TRANSLATION TECHNIQUE OF ENGLISH TO INDONESIAN SUBTITLE IN PITCH PERFECT 2 MOVIE - Novitasari Novitasari; Hosnol Wafa (JURNAL LITERASI, 2023)
This research analyzed translation technique in the subtitle of Pitch Perfect 2 movie. This research has 807 data objective of study and found 9 types of translation techniques by Molina, L. and Albir. They 1. Adaptation technique used is 25 data ( 3,1 % ), the translator change the culture element from source language to target language become close meaning, 2. Borrowing technique used is 16 data ( 2,1% ), the translator is totally use pure borrowing technique, 3. Generalization technique used is 8 data ( 1,13 % ), the translator is translate the source language in general term of something,4. Linguistic Compression technique used is 115 data ( 14,2 % ), the translator is totally compress the target language from the source language, 5.Literal Translation technique used 357 data (44,2 %), the translator is use literal meaning on this technique, 6. Modulation technique used is 144 data (17, 8% ) , the translator is change point of view in this technique 7. Reduction technique used is 57 data ( 7,1 % ), the translator is not translate the source language, but is not change the meaning and context, 8. Transposition technique used is 26 data (3,22 % ), the translator change the source language in target language in a grammatical theory and 9. Variation technique used is 58 data ( 7,1 % ). The dominant technique that used is Literal translation technique that found 355 data (44,2%).